Quality of Life and Its Association with Level of Functioning in Young Children with Cerebral Palsy - Sharawat, Indar Kumar; Panda, Prateek Kumar (Neuropediatrics, 2022)
Introduction Quality of life (QOL) in older children, adolescents, and adults with cerebral palsy (CP) is significantly impaired. Level of functioning is one of the probable determinants of impairment in QOL. However, such studies in young children with CP are scarce in the literature.Methods Parents of all consecutive children aged between 1 and 4 years with a confirmed diagnosis of CP completed the Infant Toddler Quality of Life (ITQOL) questionnaire. Total and individual subdomain scores of ITQOL were examined for association with the level of functioning measured by Gross Motor Function Classification System—Expanded & Revised (GMFCS E&R), Mini-Manual Ability Classification System (Mini-MACS), Communication Function Classification System (CFCS), and Eating and Drinking Ability Classification System (EDACS), with/without adjustment to probable confounding variables.Results One hundred three children with CP (74 boys, mean age: 2.6 ± 0.9 years, 49% lower and 39% middle socioeconomic status) were enrolled. All four scales (GMFCS, Mini-MACS, CFCS, and EDACS) describing levels of functioning had significant association with ITQOL total score (β= –0.19, –0.15, –0.11, –0.09, respectively), which persisted even after adjusting for confounding variables (p = 0.004, 0.01, 0.03, and 0.046, respectively). Among the confounding variables, uncontrolled seizures, significant vision impairment, lower socioeconomic status, type of CP, and institution of comprehensive rehabilitation measures for ≥6 months had a significant association with ITQOL score (p = 0.03, 0.04, 0.02, 0.02, and 0.01, respectively).Conclusion Level of functioning as measured by GMFCS, Mini-MACS, EDACS, and CFCS is independent predictors of impairment in QOL in young children with CP.
Keywords: cerebral palsy; children; quality of life; health-related quality of life